New Radiometric Ages for the BH-1 Hominin from Balanica (Serbia): Implications for Understanding the Role of the Balkans in Middle Pleistocene Human Evolution - Rink, William J.; Mercier, Norbert; Mihailović, Dušan; Morley, Mike W.; Thompson, Jeroen W.; Roksandic, Mirjana (PLOS ONE, 2013)
Newly obtained ages, based on electron spin resonance combined with uranium series isotopic analysis, and infrared/post-infrared luminescence dating, provide a minimum age that lies between 397 and 525 ka for the hominin mandible BH-1 from Mala Balanica cave, Serbia. This confirms it as the easternmost hominin specimen in Europe dated to the Middle Pleistocene. Inferences drawn from the morphology of the mandible BH-1 place it outside currently observed variation of European Homo heidelbergensis. The lack of derived Neandertal traits in BH-1 and its contemporary specimens in Southeast Europe, such as Kocabaş, Vasogliano and Ceprano, coupled with Middle Pleistocene synapomorphies, suggests different evolutionary forces acting in the east of the continent where isolation did not play such an important role during glaciations.